Population Diversity among Bordetella pertussis Isolates, United States, 1935–2009 - Schmidtke, Amber J. (Centers for Disease Control and Prevention, 2012)
Since the 1980s, pertussis notifications in the United States have been increasing. To determine the types of Bordetella pertussis responsible for these increases, we divided 661 B. pertussis isolates collected in the United States during 1935–2009 into 8 periods related to the introduction of novel vaccines or changes in vaccination schedule. B. pertussis diversity was highest from 1970–1990 (94%) but declined to ≈70% after 1991 and has remained constant. During 2006–2009, 81.6% of the strains encoded multilocus sequence type prn2-ptxP3-ptxS1A-fim3B, and 64% were multilocus variable number tandem repeat analysis type 27. US trends were consistent with those seen internationally; emergence and predominance of the fim3B allele was the only molecular characteristic associated with the increase in pertussis notifications. Changes in the vaccine composition and schedule were not the direct selection pressures that resulted in the allele changes present in the current B. pertussis population.